Electric drive. Dynamics. Laboratory guide study aid учебно-методическое пособие - Obraztsov, K. V. specialist in the field of electrical engineering Senior Lecturer of Tomsk Polytechnic University 1976- (TPU Publishing House, 2019)
This laboratory guide is revised and amended version of laboratory guide Electric drive. Dynamics. Laboratory guide: study aid / I.G. Odnokopylov, S.M. Semenov, 2010. The laboratory guide contains description and guidelines of four laboratory works carried out in courses Basics of an electric drive, Electric drive, Automated electric drive and is intended for students of all forms of education of Power and Electrical Engineering Program. In the guide the registration procedure for studying dynamic modes of AC and DC electric drives and static characteristics of closed systems by analytical and experimental methods using computer technology has been listed. The study aid is intended for students of direction 13.03.02 Power and Electrical Engineering.